Corporate governance practices and profitability: The Moderating effect of financing decisions - Keerthana, G.; Balagobei, S. (University of Ruhunu, 2023)
This study aims to examine the impact of corporate governance practices on profitability with the moderating effect of financing decisions on listed firms in Colombo Stock Exchange for the period from 2016 to 2020. For the data analysis, 100 listed companies from food, beverage and tobacco, capital goods, materials and consumer services sectors were selected as sample, and a quantitative technique and deductive approach were employed. Board size, board composition, CEO Duality, board gender diversity, board meeting and audit committee are proxies for corporate governance practices while profitability is measured by return on equity and return on assets. The financing decision is measured by long-term debt to total assets. Firm size and firm age are considered as control variables. Panel data regression analysis was used for data analysis. Random effect model was selected as the optimal and most appropriate model in this study. The empirical findings reveal that corporate governance is more likely to have a significant impact on firms' profitability with a moderating effect of financing decisions of listed companied in Sri Lanka.
Keywords: Board size; Board gender diversity; Financing decisions; Profitability